Crop-animal systems in Asia: Implications for research - Devendra, C. (Elsevier, 2002)
The importance of crop-animal systems in Asia, the multiple roles played by animals and the opportunities for increasing their contribution to these systems justifies continued research effort. An assessment of the role of livestock in mixed farming systems in 14 countries has identified priority systems, technical constraints and weaknesses in the national organisations. Future research needs to focus on the rain-fed production systems, where most of the livestock are found. There is an overriding need for a farming systems perspective to the research agendas that involves inter-disciplinarity and community-based participation. Such an approach will be more complex, require concentrated effort and more efficient resource use, but will be associated with considerable benefits due to a greater integration of effort.